2018
DOI: 10.2139/ssrn.3235628
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Metabolic Reactions Activated During 58-hr Fasting are Revealed by Non-Targeted Metabolomic Analysis of Human Blood

Abstract: During human fasting, metabolic markers, including butyrates, carnitines, and branched-chain amino acids, are upregulated for energy substitution through gluconeogenesis and use of stored lipids. We performed non-targeted, accurate semiquantitative metabolomic analysis of human whole blood, plasma, and red blood cells during 34-58 hr fasting of four volunteers. During this period, 44 of ~130 metabolites increased 1.5~60-fold. Consistently fourteen were previously reported. However, we identified another 30 ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 24 publications
4
24
0
Order By: Relevance
“…A recent study on mice, rats, and humans reported that fasting increases plasma uridine through a mechanism that involves uridine biosynthesis by adipocytes, whereas, in the postprandial state, liverinduced bile excretion results in plasma uridine clearance [54]. In support of this study, longer starvation times in human volunteers led to even more prominent increases in uridine plasma levels that were accompanied by a smaller rise in plasma cytidine and CTP [55]. Further confirmation came from a study where uridine as well as uracil and dihydrouracil levels in human plasma were observed to drop after food intake [56] and were also seen to be affected by circadian rhythms [56,57].…”
Section: Modulation Of Uridine Plasma Levelssupporting
confidence: 69%
“…A recent study on mice, rats, and humans reported that fasting increases plasma uridine through a mechanism that involves uridine biosynthesis by adipocytes, whereas, in the postprandial state, liverinduced bile excretion results in plasma uridine clearance [54]. In support of this study, longer starvation times in human volunteers led to even more prominent increases in uridine plasma levels that were accompanied by a smaller rise in plasma cytidine and CTP [55]. Further confirmation came from a study where uridine as well as uracil and dihydrouracil levels in human plasma were observed to drop after food intake [56] and were also seen to be affected by circadian rhythms [56,57].…”
Section: Modulation Of Uridine Plasma Levelssupporting
confidence: 69%
“…While most ERG is inside erythrocytes in whole blood (6,121,122,129,387) , there have been a number of measurements of ERG concentrations in serum. Unsurprisingly it varies with diet (388,389) , starvation (390) , age (391,392) and other factors, including diseases of oxidative stress (393) , with typical values of 20-100 μg/ml. A detailed list is provided by Cheah & Halliwell (4) ; a smaller listing is given in Table 3.…”
Section: Serum and Other Concentrationsmentioning
confidence: 99%
“…Standards for metabolite identification were purchased from commercial sources as described previously 12,26‐28 …”
Section: Methodsmentioning
confidence: 99%
“…Peak detection and identification of metabolites were performed using MZmine 2 software 29 . Detailed data analytical procedures and parameters have been described previously 26 . Normalized peak area was calculated from the following formula: Normalized peak area = (Raw peak area of each metabolite/Raw peak area of creatinine) × 1000.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation